Estudio jurídico de los efectos que se generan por la imposibilidad de sustituir la pena de presión por trabajos comunitarios en infracciones de tránsito. - Agurto Quiroga, Melisa Elizabeth (2014)
This type of penalty is of relevant importance, since it allows the offender to pay his sentence in freedom, carrying out work on transit in state institutions, at times that do not affect his family and work life, especially when he has a high social value, Constituting an exemplary penalty, which benefits the community to which the victim of the traffic violation belongs.